Determination of essential and non-essential element contents of drinking water and baby water for infant's nutrition - Demir, Funda; Ozen, Meral Yildirim; Derun, Emek Moroydor (DE GRUYTER POLAND SP Z O O, 2021)
In this study, essential (Ca, Cr, Cu, Fe, K, Mg, Na, P, Zn), and non-essential (Al, Ni, Pb) element contents of the drinking and baby water samples which are sold in the local market and tap water samples in Istanbul were examined. It was determined that elements of Cr, Cu, Fe, P, Zn, Al, and Ni were below detection limits in all water samples. Among the non-essential elements analyzed in water samples, Pb was the only detected element. At the same time, the percentages that meet the daily element requirements of infants were also calculated. As a result of the evaluations made, there is no significant difference in infant nutrition between baby waters and other drinking waters in terms of the element content.
Keywords: baby water; essential elements; non-essential elements; element consumption; FORMULAS; ZN; CD; MN; FE; PB; CU; NI; Chemistry